Understanding Muslim theology in the works of Shaykh Muhammad Ghazali - Bensaid, Benaouda; Grine, Fadila (Universiti Sains Malaysia Press, 2013)
This inquiry explores Shaykh Ghazali’s perspective on Muslim beliefs and change; and his views on how faith can sustain commitment to holistic change while assuring a favorable interaction with the intellect, without jeopardizing human freedom or the laws and patterns of the universe. This study also examines Ghazali's views on the intimate connection of Muslim beliefs to life in addition to his ideas on the reform of theological instruction as an effective means of re-shaping the intellectual identity of Muslims and actualizing change in contemporary Muslim societies. The study of Ghazali’s intellectual analysis on Muslim faith and change is vital to understanding the current debate on religion, reform and modernity, particularly as he addresses many problems and issues pertaining to the methodology of religious understanding and practice within the very context of Muslim life.